EFL STUDENTS CHALLENGES AND STRATEGIES IN LEARNING SPEAKING AT ENGLISH DEPARTMENT STATE ISLAMIC UNIVERSITY OF MATARAM - Tawali (Journal of English Education and Literature, 2024)
Speaking is a tool to communicate with other people. With speaking ability, EFL students will be fluent at communication and sharing information with other people especially in an academic context. Therefore, this research aimed to find out EFL students challenges during learning speaking, students strategies in learning speaking, and students strategies in solving the challenges in learning speaking at English Department State Islamic University of Mataram. This research used a mixed-methods research design (quantitative and qualitative) and involved 16 EFL students at the English Department as informants. The data were obtained by using a questionnaire and a semi-structured interview. The result of this research showed that students faced challenges during learning speaking, such as; Lack on Vocabulary, Difficult in achieving Speaking Fluency, Limited exposure to English, Fear of making mistakes, and Lack on overcoming nervousness. Meanwhile, there were strategies students used in learning speaking, such as; Join a Speaking Club, Watching Movies/Series in English, Regular Spoken Language Practice, Conversation  With Native Speakers, Using Speaking Learning Apps, and Reading Book/News in English. However researcher also found students strategies to overcome the challenges they faced during leaning speaking, such as: Use Social Media, Practice Speaking in Front of the Mirror, Learn from Song, Debate and Speaking English with Partners.